Identification of chemical constituents in the extracts of pleurotus giganteus (Berk.) Karunarathna & K. D. Hyde / Seamus Moroney - Moroney, Seamus (2013)
Pleurotus giganteus mushroom is used for culinary purposes by the indigenous people (Orang Asli) in Malaysia for food. The present study was undertaken to extract and profile the bioactive metabolites in the fruiting bodies of the cultivated mushroom. Various chemical solvents were used in this investigation because different compounds were extracted by different solvents based on the solvent’s polarity. The solvents employed were methanol, hexane, ethyl acetate, distilled water and butanol. The ethyl acetate and hexane extracts were then subjected to flash column chromatography with stepwise addition of hexane and acetone. The identification of compounds in the sub-fractions from ethyl acetate and hexane extracts were done using GC-MS and LC-MS/MS analyses. Twenty seven secondary metabolites namely fatty acids such as pal-mitic acid and oleic acid; fatty acid methyl esters such as methyl linoleate; phenolics such as caffeic acid and cinnamic acid; sterols such as ergosterol and neoergosterol; organic acids such as succinic acid and alkaloids such as N-acetylphenylethylamine were identified. Extraction of the flavour components (essential oil) was also performed. Benzyl alcohol was identified to be present in the essential oil. To our knowledge this is the first report of chemical components from the fruiting bodies of Pleurotus giganteus.